M‐sequence‐based ultra‐wideband sensor network for vitality monitoring of elders at home. Issue 2 (1st February 2015) - Sachs, Jürgen; Herrmann, Ralf
Abstract : The western societies are increasingly faced with the challenges of enabling a self‐determined and safe life for a growing number of elderly people. Remote monitoring of vitality is an important tool for health risk mitigation but many of the current methods either deliver only infrequent information or require conscious cooperation of the senior. The authors propose an ultra‐wideband (UWB) radio sensor network based on M‐sequence technology specifically designed for the vitality monitoring of persons living alone. It uses the frequency band in the range from 6 to 8.5 GHz (electronic communications committee (ECC)‐band), and provides precise localisation, captures breathing motion during rests, can be used for fall detection and allows the extraction of gait features. The sensor network can be installed in common living spaces. It operates continuously in the background without any user interaction. Vitality monitoring by radar sensors is based on motion detection and tracking. This poses some challenges to radar devices because of the harsh multi‐path conditions in apartments. This study discusses these challenges, illustrates how to meet them and gives examples for vitality features which can be extracted from UWB‐radar data.